(untitled) (International Journal of Engineering and Computer Science, 2014)
In the modern era of computing, wireless network plays vital role in building a strong infrastructure for faster and improved communication. Recent developments in the field of sensor devices have broadened the area of sensor networks, which leads to new protocol design, specifically for energy consumption with wireless sensor networks (WSNs). These sensor nodes are low power, light weighted and energy efficient.WSNs with hundreds or thousands of sensor nodes can sense data from multiple locations and forward it to a particular user’s location. Such data are routed using several routing algorithms. In this work, we discuss the several routing aspects in regards to the energy model of wireless sensor networks for IEEE 802.15.4. Further, This IEEE 802.15.4 standard contain two types of devices first one is FFD that if Fully Functional Device. This device is further classified into three categories PAN coordinator, Coordinator and Devices. And also compare the results of default AODV with modified AODV to make energy consumption efficient.